Effect of supplementation with extract of white bean flour in murine model - Marques, Emília Torres Costa; Coelho, Patrizia Mello; Paula, Alessandra Teixeira de; Bastos, Daniel Silva Sena; Almeida, Palloma Porto; Oliveira, Leandro Licursi de; Cardoso, Silvia Almeida (Ciência e Natura, 2022)
Common bean supplementation (Phaseolus vulgaris) "in natura" causes loss of body weight associated with a deficiency in nutrient absorption and histopathological changes. This effect has been attributed to phytohemagglutinin (PHA) present in high concentrations in red and white beans. The main objective of this work was to evaluate the safety of white bean flour as a dietary supplement. Animals were treated for 14 days with extract of white bean flour (WBFE) at doses of 2.65g/kg and 5.30g/kg. A significant reduction in body weight was observed, accompanied by the reduction of mean values of glycemia, in both groups in relation to the control group. Significant structural changes were also observed in the intestinal epithelium. Additionally, mice treated with WBFE 5.30g/kg presented mononuclear inflammatory infiltrate in the lamina propria of the intestinal mucosa accompanied by a dose-dependent increase in the dosage of chemokine MCP-1 and nitric oxide, although without causing intestinal and hepatic oxidative and oxidative damage. The deleterious effects resulting from the use of the WBFE are not permanent since the treated animals after 14 days without WBFE stimuli. In conclusion, commercial bean flour did not prove to be safe as oral dietary supplementation at the dosages used because of the antinutritional and immunomodulatory effects.